The Visionary Leadership of the School Principal for Improving the Quality of Education - Moh, Masnun (Journal of Ecohumanism, 2024)
The progress or decline of an institution is determined by the leadership style. Likewise, in educational institutions such as schools, schools will experience rapid progress if the leader has the right leadership style. One leadership style to improve quality and quality is a visionary leadership style. Improving the quality and quality of education in school institutions is very difficult if it is not accompanied by improving teacher performance. This is because teachers are the most determining component in the education system as a whole which must receive central attention. This visionary leadership can have a significant influence on improving teacher performance because the driving school principal can provide a clear vision and can implement the vision he has created for the teacher’s future so by increasing teacher performance it is hoped that there will also be an increase in the quality and quality of education. The driving school principal acts as the central force that is the driving force of school life. For schools to be able to compete, driving school principals must be committed to change by carrying out their role as school principals, and must always be ready and dynamic for change; Changing Constituent Needs. The school principal’s visionary leadership and teacher’s teaching performance have a positive and significant influence on school effectiveness in primary and secondary schools. This indicates that school effectiveness is determined by the driving school principal’s visionary leadership and the teacher’s teaching performance together. The better the school principal’s visionary leadership and the teacher’s teaching performance, the better and better the school’s effectiveness will be.